Business Expansion Proposal of Agnice Fire Protection - Manappat, Suhail Ameer; Suresh Babu, Sruthy (2010)
Agnice Fire Protection Limited, founded in 1995, is one of the major Engineering, Procurement and Construction (EPC) companies in the Fire Protection domain in India. The company is Headquartered in Chennai and has six other offices across India, including, Delhi, Mumbai, Bangalore and Kolkata. The major sectors served are Energy & Power, Infrastructure, Oil & Gas and other industrial sectors, with key clients like Technip, Essar, ABB, Larsen & Toubro, Dupont, Indian Oil Corporation, Tata and Reliance etc. The company is a tier 1 supplier to these companies and provide end to end solution staring from engineering to installation of the fire detection and protection systems. The company is in a growth path today and as a part of its expansion plans has managed to raise a substantial amount of investment from a private investor to aide its expansion. The company has set its goal to make different verticals of specific roles so that all put together it becomes a major player in the engineering segment. Another important step is to move out of the Indian market and expand into the Middle East and Northern African markets. The development plans of the company are outlined below briefly. • Setting up of an Engineering and design consultancy for Fire and Security systems • Setting up of a manufacturing facility for fire protection equipments • Acquiring a company in the Security systems business • Acquiring a company in the Mechanical and Electrical Utilities business • Expansion of current business internationally to the Middle East All the above plans are intended to increase the top line of the company considerably and also the profit margins. Adding new verticals like the engineering consultancy and the manufacturing facility will allow Agnice to significantly expand profit margins. The Company has executed over 250 turnkey projects for various client segments such as power, steel, oil & gas, commercial complexes etc. The Company has an experienced professional management team, and has built a good track record in execution of fire protection system projects.